How Do Reference Points Influence the Representation of the N200 for Consumer Preference? - Wang, Guangrong; Li, Jianbiao; Zhu, Chengkang; Wang, Shenru; Jiang, Shenzhou (Frontiers in Psychology, 2021)
Recent studies have suggested that event-related brain potential (ERP) can represent consumer preference, and there is consensus that the N200 is the best indicator of consumer preference. Measurement of reference-dependent consumer preference, in turn, requires a reference point, but it remains largely unknown how reference points modulate the preference-related N200. We designed an experiment to investigate how reference points affect the N200 based on classical paradigms. In the single-reference condition, one product was displayed in each trial; in the conjoined-reference condition, a pair of products was displayed simultaneously. Our results showed that in the single-reference condition, low-preference products elicited more negative N200 than high-preference products, replicating previous results, but the N200 could not distinguish between low- and high-preference products when viewing two options of similar subjective value in the conjoined-reference condition. These findings suggest that reference points modulate representation of the N200 on consumer preference. When only viewing one product, participants make a value judgment based on their expectation, however, when viewing two products simultaneously, both their expectation and the alternative product can serve as reference points, and whether the N200 can represent consumer preference depends on which reference point is dominant. In future research, reference points must be controlled when the N200 is used to explore value-related decision making.